(untitled) (Research, Society and Development, 2021)
The pandemic Coronavirus 2019-nCoV (COVID-19) outbreak is target of research to understand its consequences in patients with neurological diseases, such as Parkinson’s disease. This article aims to discuss the evidence in scientific literature about the risks and complications of the COVID-19 pandemic on Parkinson’s patients. Searches for articles in English, Portuguese or Spanish were carried out using the PubMed, PubMed, Lilacs, ScienceDirect and SciElo databases, using the associated descriptors: “Coronavirus Infections” OR “COVID-19”AND “Parkinson Disease” about years 2019 and 2020. 268 results were found that, after applying inclusion and exclusion criteria, were reduced to 23 articles. The analysis indicates that the pandemic contributes to psychological stress and is related to the worsening of non-motor and motor symptoms. Symptoms are aggravated by difficulties in health care access, access to medications and maintenance of specialized treatments. In patients with COVID-19 infection, this can lead to immune dysregulation, neuronal death and changes in dopaminergic metabolism, in addition to inflammatory activation that could worsen synucleinopathy. Parkinson’s disease itself does not represent an increased risk of infection, however the average age of patients and comorbidities in this group are factors that increase the chances of hospitalization and death after contracting COVID-19. In this perspective, protective strategies such as physical exercise, physiotherapy, psychosocial dynamics and telemedicine tools are essential and must be adapted to promote health care in times of isolation.